GA(2)LEN skin test study II: clinical relevance of inhalant allergen sensitizations in Europe - Burbach, G. J.; Heinzerling, L. M.; Edenharter, G.; Bachert, C.; Bindslev-Jensen, C.; Bonini, S.; Bousquet, J.; Bousquet-Rouanet, L.; Bousquet, P. J.; Bresciani, M.; Bruno, A.; Canonica, G. W.; et al. (Allergy, 2009)
Skin prick testing is the standard for diagnosing IgE-mediated allergies. A positive skin prick reaction, however, does not always correlate with clinical symptoms. A large database from a Global Asthma and Allergy European Network (GA(2)LEN) study with data on clinical relevance was used to determine the clinical relevance of sensitizations against the 18 most frequent inhalant allergens in Europe. The study population consisted of patients referred to one of the 17 allergy centres in 14 European countries (n = 3034, median age = 33 years). The aim of the study was to assess the clinical relevance of positive skin prick test reactions against inhalant allergens considering the predominating type of symptoms in a pan-European population of patients presenting with suspected allergic disease.|Clinical relevance of skin prick tests was recorded with regard to patient history and optional additional tests. A putative correlation between sensitization and allergic disease was assessed using logistic regression analysis.|While an overall rate of >or=60% clinically relevant sensitizations was observed in all countries, a differential distribution of clinically relevant sensitizations was demonstrated depending on type of allergen and country where the prick test was performed. Furthermore, a significant correlation between the presence of allergic disease and the number of sensitizations was demonstrated.|This study strongly emphasizes the importance of evaluating the clinical relevance of positive skin prick tests and calls for further studies, which may, ultimately, help increase the positive predictive value of allergy testing.
Keywords: Adult Allergens Animals Cats Dogs Europe Humans Hypersensitivity Hypersensitivity; Immediate Inhalation Exposure Plant Proteins Poaceae Skin Tests